Design and Simulation of a Synchronous Reference Frame-Based Active Power filter for Harmonic Mitigation - Olusegun A. AFOLABI; Olanrewaju A. OLANITE; Nsikan L. AKPAN (FUDMA Journal of Engineering and Technology, 2026)
The daily increase in the application of power electronics in modern devices is of serious concern. Power electronic or non-linear load devices such as battery charging systems, draw non-sinusoidal currents which tend to have a detrimental impact on the power quality of distribution systems. The use of these devices badly distorts the current waveforms in the system’s supply. In order to reduce harmonic distortion in a three-phase distribution system delivering nonlinear loads, this study examines the design and performance of a shunt Active Power Filter (APF). Power quality and system efficiency are negatively impacted by the substantial current harmonics introduced by the growing prevalence of power electronic devices. To address this issue, an APF based on synchronous reference frame (SRF) control is developed and implemented in a 3-phase, 11 kV/400 V, 500 kVA system. By using hysteresis current control and Synchronous Reference Frame (dq0) transformation, the suggested control approach allows for precise harmonic component extraction and correction.MATLAB/Simulink is used to assess the system performance, and the Fast Fourier Transform (FFT) is used for harmonic analysis. Total Demand Distortion (TDD) and individual harmonic limitations are used to evaluate compliance with IEEE 519 standards. According to simulation results, TDD significantly decreased from 24.76% to 0.73%, much below the recommended 8% limit. The results verify that the suggested APF arrangement is successful in delivering high-quality power under nonlinear loading circumstances.